A study of fly-ash and slag based alkali activated binder using sea water based alkaline activator - Ratna Bhanu, Tadicharla V.K.; Rao, T.D. Gunneswara (Journal of Structural Engineering, 2024)
This paper presents investigation in alkali activated paste and alkali activated mortar produced by combinations of fly ash collected from coal based thermal power plant and ground granulated blast furnace slag collected from steel manufacturing facilities. The fly ash and ground granulated blast furnace slag are industrial by-products rich in aluminosilicates. The present study focuses on effect of utilization of seawater-based alkaline activator solution in alkali activated paste and mortar. Alkaline activator solution activates the chemical processes in binder materials when used in right concentrations and right proportion. This paper discusses the mechanical properties and microstructure characteristics of seawater-based alkali activated paste and mortar in comparison with conventional distilled waterbased alkali activator. The usage of sea water shown insignificant change in setting times and compressive strengths for various combinations of binder material. The microstructure analysis also showed less variation in mineralogical formations when conventional distilled water is replaced with sea water in preparation of alkaline activator solution.